Assessment of Groundwater Potential and Suitable Borehole Locations in Esan Central Using Remote Sensing and Geospatial Analysis - Oladosu, Stephen Olushola; Eghemenrior Alenkhe, Mabel; Isesele, Obehi; Muhammad, Tijjani Yusuf (Program Pascasarjana Universitas Sriwijaya, 2025)
Groundwater potential zone mapping is essential for identifying optimal sites for sustainable water infrastructure. This study presents a novel integration of ten environmental factors using remote sensing and GIS-based Analytical Hierarchy Process (AHP) to delineate groundwater potential zones and suitable borehole sites in Esan Central Local Government Area (LGA), Edo State, Nigeria. Unlike previous studies that focused on fewer variables, this research incorporates slope, geology, rainfall, drainage density, lineament density, land use/land cover, elevation, soil type, and proximity to infrastructure. The model was validated using 43 ground-truth locations with an overall accuracy of 85.3% and a Kappa coefficient of 0.78. Results showed that the majority of the area (65.2%) falls under moderate groundwater potential, while only 0.06% lies in the very high category. Borehole suitability analysis identified 43 optimal drilling locations. These findings provide actionable insights for planners and water agencies aiming to improve rural water access through scientifically grounded siting decisions.